1983
DOI: 10.1007/bf00427826
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine does not improve discrimination of brain stimulation reward by rats

Abstract: Rats were trained to shuttle between two selected ("ON") arms of a Y maze, to obtain electrical stimulation of the medial forebrain bundle. Each shuttle response was rewarded with a brief pulse train. Repetitive entries into the same "ON" arm were not rewarded, nor were entries made into the third ("OFF") arm. Every 67s, stimulation was made available from a different pair of arms. Test sessions lasted for 80 min, beginning immediately after SC injection. Undrugged subjects responded faster, and with a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Together, these results suggested that muscarinic receptor activation inhibits ICSS, whereas nicotinic receptor activation both faciiitates and inhibits VTA ICSS in a dose-dependent manner. This conc!usion is consistent with previously reported effects of cholinergic drugs on both VTA and LH ICSS (O!ds and Domino I969 ;Newman 1972;Clarke and Kumar 1983;Schaefer and Michael i986).…”
Section: Discussionsupporting
confidence: 93%
“…Together, these results suggested that muscarinic receptor activation inhibits ICSS, whereas nicotinic receptor activation both faciiitates and inhibits VTA ICSS in a dose-dependent manner. This conc!usion is consistent with previously reported effects of cholinergic drugs on both VTA and LH ICSS (O!ds and Domino I969 ;Newman 1972;Clarke and Kumar 1983;Schaefer and Michael i986).…”
Section: Discussionsupporting
confidence: 93%
“…Initial evidence came from studies of brain stimulation reward, where both amphetamine (Stein and Ray 1960;Stein 1961) and cocaine (Crow 1970) lowered thresholds for brain self-stimulation reward in rats. A comparable impact of nicotine on brain stimulation reward has also been demonstrated (Ivanova and Greenshaw 1997;Bozarth et al 1998a;Bozarth et al 1998b; but see also Clarke and Kumar 1983). In particular, nicotine was shown to induce parallel leftward shifts in rate-frequency functions for both lateral hypothalamic and midline mesencephalic brain stimulation, which could reflect a synergism between nicotine and the reinforcing properties of brain stimulation (Bauco and Wise 1994).…”
Section: Psychostimulants Increase Conditioned Reinforcementmentioning
confidence: 63%
“…For example, we have shown that rats readily selfadminister a b2-selective nicotinic receptor agonist (Liu et al, 2003). Conversely, nicotinic receptor antagonists have been found to block nicotine's effects on striatal dopamine release and turnover (Haikala and Ahtee, 1988;Nisell et al, 1994), nicotine-induced dopaminergic signaling and neuronal excitation (Hamada et al, 2004;Yin and French, 2000), the locomotor effects of nicotine (Clarke and Kumar, 1983;Curzon et al, 1996;Kuo et al, 1999), and nicotine-induced hypothermia (Haikala and Ahtee, 1988;Zarrindast et al, 2001). Similarly, nicotinic antagonists precipitate nicotine withdrawal (Adams and Cicero, 1998;Hildebrand et al, 1999;Watkins et al, 2000b) and decrease rates of nicotine self-administration (Corrigall and Coen, 1989;Donny et al, 1999;Shoaib et al, 1997;Watkins et al, 1999).…”
Section: Introductionmentioning
confidence: 99%